RAS mutation analysis in circulating tumor DNA from patients with metastatic colorectal cancer: the AGEO RASANC prospective multicenter study - Bachet, J.B.; Bouché, O.; Taieb, J.; Dubreuil, O.; Garcia, M.L.; Meurisse, A.; Normand, C.; Gornet, J.M.; Artru, P.; Louafi, S.; Bonnetain, F.; Thirot-Bidault, A.; et al. (Annals of oncology, 2018)
RAS mutations are currently sought for in tumor samples, which takes a median of almost 3weeks in western European countries. This creates problems in clinical situations that require urgent treatment and for inclusion in therapeutic trials that need RAS status for randomization. Analysis of circulating tumor DNA might help to shorten the time required to determine RAS mutational status before anti-epidermal growth factor receptor antibody therapy for metastatic colorectal cancer. Here we compared plasma with tissue RAS analysis in a large prospective multicenter cohort. Plasma samples were collected prospectively from chemotherapy-naive patients and analyzed centrally by next-generation sequencing (NGS) with the colon lung cancer V2 Ampliseq panel and by methylation digital PCR (WIF1 and NPY genes). Tumoral RAS status was determined locally, in parallel, according to routine practice. For a minimal κ coefficient of 0.7, reflecting acceptable concordance (precision±0.07), with an estimated 5% of non-exploitable data, 425 subjects were necessary. From July 2015 to December 2016, 425 patients were enrolled. For the 412 patients with available paired plasma and tumor samples, the κ coefficient was 0.71 [95% confidence interval (CI), 0.64–0.77] and accuracy was 85.2% (95% CI, 81.4% to 88.5%). In the 329 patients with detectable ctDNA (at least one mutation or one methylated biomarker), the κ coefficient was 0.89 (95% CI, 0.84–0.94) and accuracy was 94.8% (95% CI, 91.9% to 97.0%). The absence of liver metastases was the main clinical factor associated with inconclusive circulating tumor DNA results [odds ratio=0.11 (95% CI, 0.06–0.21)]. In patients with liver metastases, accuracy was 93.5% with NGS alone and 97% with NGS plus the methylated biomarkers. This prospective trial demonstrates excellent concordance between RAS status in plasma and tumor tissue from patients with colorectal cancer and liver metastases, thus validating plasma testing for routine RAS mutation analysis in these patients. Clinicaltrials.gov, NCT02502656.